Confirming the structure of negative beliefs about psychosis and bipolar disorder: A confirmatory factor analysis study of the Personal Beliefs about Experience Questionnaire and Personal Beliefs about Illness Questionnaire. (6th March 2015) - Taylor, Peter J.; Pyle, Melissa; Schwannauer, Matthias; Hutton, Paul; Morrison, Anthony
<x xml:space="preserve">Abstract</x> Objectives Negative beliefs about psychosis and other mental health difficulties may contribute to depression and distress in individuals with these experiences. The Personal Beliefs about Experience Questionnaire (PBEQ) and Personal Beliefs about Illness Questionnaire (PBIllQ) are two widely used measures of these beliefs. It is currently uncertain how the items on these measures map onto different underlying factors. This study therefore aimed to test the factor structure of these two measures. Methods Confirmatory factor analysis (CFA) was used to test three alternative, pre‐specified, factor structures for the PBIllQ and PBEQ in a sample of individuals diagnosed with bipolar disorder (n = 202) and a sample of individuals with experien‐ces of psychosis (n = 362). Associations with depressive symptoms were also examined. Result A three‐factor structure was supported for both measures, which included Negative Expectations/Appraisals (NEA), Internal Shame/Defectiveness (ISD) and External Shame (ES) factors. The NEA and ISD subscales also had consistent independent associations with depressive symptoms. Conclusions The results suggest that the PBIllQ and PBEQ may capture three distinct sets of negative beliefs in individuals with psychosis or bipolar disorder and that these beliefs may have important consequences for subsequent difficulties in these populations such as depression. Both measures may be helpful in supporting assessment and formulation in clinical practice and in evaluating belief change in intervention trials. However, when used in these settings, the three subscales identified in this study may be the most valid way of calculating scores on these measures. Practitioner points Negative personal beliefs about the causes, meaning and consequences of psychosis and bipolar disorder are associated with greater distress and depression. Two related measures, the PBIllQ and PBEQ, have been developed to assess these beliefs. Our analyses suggest that scores on these questionnaires are best broken down into three subscales which capture perceptions of internal shame or defectiveness, general negative appraisals and perceptions of external shame. These subscales may capture key underlying sets of negative beliefs within individuals with psychosis or bipolar disorder, which in turn impact upon well‐being, such as being associated with greater depression. These subscales can be used to aid assessment and formulation within clinical practice but may also provide a valuable means of assessing changes in negative beliefs following interventions.